EpCAM as multi-tumour target for near-infrared fluorescence guided surgery. Issue 1 (December 2016) - van Driel, P.; Boonstra, M.; Prevoo, H.; van de Giessen, M.; Snoeks, T.; Tummers, Q.; Keereweer, S.; Cordfunke, R.; Fish, A.; van Eendenburg, J.; Lelieveldt, B.; Dijkstra, J.; et al.
Abstract Background Evaluation of resection margins during cancer surgery can be challenging, often resulting in incomplete tumour removal. Fluorescence-guided surgery (FGS) aims to aid the surgeon to visualize tumours and resection margins during surgery. FGS relies on a clinically applicable imaging system in combination with a specific tumour-targeting contrast agent. In this study EpCAM (epithelial cell adhesion molecule) is evaluated as target for FGS in combination with the novel Artemis imaging system. Methods The NIR fluorophore IRDye800CW was conjugated to the well-established EpCAM specific monoclonal antibody 323/A3 and an isotype IgG1 as control. The anti-EpCAM/800CW conjugate was stable in serum and showed preserved binding capacity as evaluated on EpCAM positive and negative cell lines, using flow cytometry and cell-based plate assays. Four clinically relevant orthotopic tumour models, i.e. colorectal cancer, breast cancer, head and neck cancer, and peritonitis carcinomatosa, were used to evaluate the performance of the anti-EpCAM agent with the clinically validated Artemis imaging system. The Pearl Impulse small animal imaging system was used as reference. The specificity of the NIRF signal was confirmed using bioluminescence imaging and green-fluorescent protein. Results All tumour types could clearly be delineated and resected 72 h after injection of the imaging agent. Using NIRF imaging millimetre sized tumour nodules were detected that were invisible for the naked eye. Fluorescence microscopy demonstrated the distribution and tumour specificity of the anti-EpCAM agent. Conclusions This study shows the potential of an EpCAM specific NIR-fluorescent agent in combination with a clinically validated intraoperative imaging system to visualize various tumours during surgery.